2022
DOI: 10.1371/journal.pone.0273507
|View full text |Cite
|
Sign up to set email alerts
|

Functions of block of proliferation 1 during anterior development in Xenopus laevis

Abstract: Block of proliferation 1 (Bop1) is a nucleolar protein known to be necessary for the assembly of the 60S subunit of ribosomes. Here, we show a specific bop1 expression in the developing anterior tissue of the South African clawed frog Xenopus laevis. Morpholino oligonucleotide-mediated knockdown approaches demonstrated that Bop1 is required for proper development of the cranial cartilage, brain, and the eyes. Furthermore, we show that bop1 knockdown leads to impaired retinal lamination with disorganized cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(15 citation statements)
references
References 99 publications
7
8
0
Order By: Relevance
“…The domains of three genes expressed in the neural plate (sox2, sox11, irx1) were each broader on the MO-injected side in a high percentage of embryos (Figure 1a-c). This is consistent with the expansion of another neural plate marker, sox3, at earlier neural ectodermal stages, as reported by Gärtner et al (2022); interestingly, these authors did not observe expansion of sox2 at this earlier stage, perhaps because it is not upregulated by sox3 until neural plate stages (Rogers et al, 2009). Conversely, the gene expression domains of the epidermal border (dlx5), neural crest (foxd3, sox9), and preplacodal ectoderm (six1, sox11, irx1, sox9) were each reduced on the MO-injected side compared to the control side (Figure 1d-j).…”
supporting
confidence: 91%
See 2 more Smart Citations
“…The domains of three genes expressed in the neural plate (sox2, sox11, irx1) were each broader on the MO-injected side in a high percentage of embryos (Figure 1a-c). This is consistent with the expansion of another neural plate marker, sox3, at earlier neural ectodermal stages, as reported by Gärtner et al (2022); interestingly, these authors did not observe expansion of sox2 at this earlier stage, perhaps because it is not upregulated by sox3 until neural plate stages (Rogers et al, 2009). Conversely, the gene expression domains of the epidermal border (dlx5), neural crest (foxd3, sox9), and preplacodal ectoderm (six1, sox11, irx1, sox9) were each reduced on the MO-injected side compared to the control side (Figure 1d-j).…”
supporting
confidence: 91%
“…Thus, the embryonic expression data suggest an additional, developmental function for Bop1, consistent with reports that other proteins involved in ribosomal biogenesis, such as Pes1 and Ppan, have additional developmental functions including regulating gene expression in neural and pronephric tissues (Bugner et al, 2011;Gessert et al, 2007;Tecza et al, 2011). Recently, Gärtner et al (2022) demonstrated that Bop1 also is required for establishing the size of the tadpole brain, retina and cranial cartilages, as well as controlling the levels of gene expression in embryonic brain and retina. They also provided evidence that these effects are likely independent of a ribosomal biogenesis or cell proliferation function, which is consistent with the idea that Bop1 performs multiple functions, sometimes referred to as protein "moonlighting" (Jeffery, 2018).…”
supporting
confidence: 87%
See 1 more Smart Citation
“…For example, mutations in SBDS are associated with Schwachman-Diamond syndrome (Boocock et al 2003) and defects in RBM28 cause alopecia, neurological defects, and endocrinopathy (ANE) syndrome (Nousbeck et al 2008;McCann et al 2016;Bryant et al 2021). Intriguingly, RSL24D1 was recently reported to be required for murine embryonic stem cell proliferation (Durand et al 2021) and BOP1 in Xenopus anterior development (Gartner et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it has been shown that PES1 is required for zebrafish and mouse embryonic development (Allende et al 1996;Lerch-Gaggl et al 2002) and more specifically Xenopus neural crest cell migration (Gessert et al 2007). The cranial cartilage defects observed in Xenopus upon loss of BOP1 (Gartner et al 2022) and PES1 (Gessert et al 2007) are hallmarks of ribosomopathies (Farley-Barnes et al 2019). It will be of interest to further dissect the roles of RSL24D1 and PeBoW in ribosome biogenesis as it relates to embryonic development in vertebrates.…”
Section: Discussionmentioning
confidence: 99%